PROVISION OF MICRO CREDIT AT BANK MANDIRI BOGOR WITH THE FUZZY TSUKAMOTO METHOD - Susliansyah Susliansyah; Nisan Nisan; Heny Sumarno; Hendro Priyono; Linda Maulida (Jurnal Techno Nusa Mandiri, 2020)
It is an advantage for the bank, in this case, the Bank Mandiri Dramaga1 Bogor Unit, because of the increasing credit activity in banks, it is necessary to have an assessment in credit as consideration for prospective customers before the bank decides to accept or reject a prospective customer request. So it is necessary to develop a method that can assist and facilitate the bank in making decisions quickly and accurately. The basis for decision making is based on the criteria for determining who is eligible or not to receive a loan. To assist in determining whether someone is eligible or not to receive a loan, a decision support system is needed using fuzzy logic and applying the Tsukamoto method. The Lending Decision Support System was created to assist and facilitate the bank in making decisions to provide alternatives if a prospective customer applies for credit is accepted or not.